1995
DOI: 10.1007/bf00309783
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA sequences reveal close relationships between social parasitic ants and their host species

Abstract: In the tribe Leptothoracini, the phylogenetic relationship of socially parasitic ants (Doronomyrmex kutteri, D. goesswaldi and Harpagoxenus sublaevis) and their host species Leptothorax acervorum has been controversial. Even more controversial is the relationship between the socially parasitic ant Chalepoxenus muellerianus and its host species Leptothorax unifasciatus, L. nigriceps, L. interruptus and L. recedens. On the basis of morphological, ecological and ethological criteria it has been argued that social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…For example, it could explain how the social parasite A. insinuator could have evolved from its host, A. echinatior (Bekkevold and Boomsma, 2000;Schultz et al, 1998) by sympatric speciation. The close phylogenetic affiliation of ant social parasites and their hosts (Schultz et al, 1998) is known as Ă”EmeryĂ•s ruleĂ• (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986) and while sympatric speciation is often invoked to explain this pattern (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986), it hard to see how it could arise in the absence of a clear mechanism. Incompatibility between multiple Wolbachia types within a population could provide such a mechanism (Hurst and Schilthuizen, 1998;Stouthamer et al, 1999;Werren, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it could explain how the social parasite A. insinuator could have evolved from its host, A. echinatior (Bekkevold and Boomsma, 2000;Schultz et al, 1998) by sympatric speciation. The close phylogenetic affiliation of ant social parasites and their hosts (Schultz et al, 1998) is known as Ă”EmeryĂ•s ruleĂ• (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986) and while sympatric speciation is often invoked to explain this pattern (Baur et al, 1995(Baur et al, , 1996Buschinger, 1986), it hard to see how it could arise in the absence of a clear mechanism. Incompatibility between multiple Wolbachia types within a population could provide such a mechanism (Hurst and Schilthuizen, 1998;Stouthamer et al, 1999;Werren, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Heinze et al (1995a) found no differences between our material from Spain and central European L. acervorum in a couple of diagnostic isozymes. There was also a close similarity between this population and ordinary, facultatively polygynous L. acervorum from the Pyrenees in a cytochrome b DNA sequence analyzed by Baur et al (1995), though a central European and even more a Japanese population (Ito, 1990) differed markedly. As long as it remains uncertain whether the population from central Spain really belongs to L. acervorum, or perhaps represents a subspecies of the latter, it shall be provisionally named "L. acervorum Albarracin".…”
Section: Introductionmentioning
confidence: 92%
“…These results form an excellent framework for the study of dolichoderine behavior and systematics, but require testing and extension, especially given that several nodes had very low confidence. Molecular phylogenetic studies of ants are relatively rare so far (Ayala et al, 1996;Baur et al, 1993Baur et al, , 1995Baur et al, , 1996Crozier et al, 1995;Wetterer et al, 1998), although ant sequences have been included in studies of families and orders and, in combination with fossil dating, have yielded an estimate of the time of origin of the group as falling into the Jurassic . The only molecular phylogenetic study of dolichoderine ants was restricted to species of Azteca (Ayala et al, 1996).…”
Section: Introductionmentioning
confidence: 99%